PENGARUH KURIKULUM MERDEKA DALAM PEMBELAJARAN: SEBUAH KAJIAN LITERATUR - Hadi, A. Ikhlas Muhtar; Pahrudin, Agus; Jatmiko, Agus; Koderi, Koderi (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
The aim of this research is to analyze and find out the general picture of the influence of the independent curriculum on learning. The research method used in this research is a literature review, where this method is research that uses secondary data sources. Based data was obtained using the help of the Publish or Perish reference search tool with the keyword